Nutritional Profiling of Wild Edible Plants: Quantification of Macronutrients and Minerals via Energy Dispersive X-ray (EDX) Fluorescence Spectroscopy - Muhammad Ibrahim; Naveed Akhtar; Asghar Khan; Sara; Yasir Anwar; Ling Shing Wong; Vetriselvan Subramaniyan; Vinoth Kumarasamy; Abdur Rauf; Yogesh Kumar Ahlawat; Nisha Sharma; Luciano de Almeida Lopes (Brazilian Journal of Biology)
Abstract The wild edible plants offer a valuable resource for food and human nutrition. The current study aimed to analyze the proximate composition and ethno-medicinal profiles of twenty selected wild edible plants from the Malakand District, Pakistan. The proximate composition (moisture, ash, crude protein, crude fat, and dietary fiber) was analyzed following Association of Official Agricultural Chemists (AOAC) protocols. Ethno-medicinal profiles were obtained through semi-structured interviews with local informants. Mineral elements were analyzed using Energy Dispersive X-ray Fluorescence (EDX) Spectroscopy. The normalized variation matrix and centered log ratio (CLR) biplot were used to assess linear associations between nutritional components. The results revealed significant variations in the nutritional components and mineral contents among the studied plant species. Higher crude carbohydrates (64.48%) were scrutinized in Ziziphus jujuba, followed by proteins (19.90%) in leaves of Solanum nigrum, fiber (19.50%) in Caralluma tuberculata and fats (6.12%) in Mentha spicata. A maximum energy value of 332.34 Kcal/100g was calculated for leaves of Solanum nigrum. The concentrations of carbon (C) in Mentha longifolia were (60.20%), followed by oxygen (46.06%) in Ziziphus jujuba, potassium (10.80%) in Rumex dentatusand nitrogen (7.98%) in Nasturtium officinale. The centered log ratio biplot confirms strong relationships between moisture, energy, carbohydrates, fibers, and ash content, while protein and fat concentrations exhibit a separate pattern. The findings provide valuable insights into the compositional data analysis of edible plant species, suggesting interdependencies among carbohydrate, energy, moisture content, and fibers. Additionally, the results of our current study showed that all of these selected wild edible plants have the potential to provide humans with important macronutrients and elements.